The effect of intraparenchymal blood patching on the rate of pneumothorax in patients undergoing percutaneous CT-guided core biopsy of the lung. Issue 116 (July 2019) - Perl, R.M.; Risse, E.; Hetzel, J.; Bösmüller, H.; Kloth, C.; Fritz, J.; Horger, M.
Abstract: Purpose: To assess the effect of intraparenchymal blood patching (IBP) as well as tumor- and operator-related risk factors on the rate of pneumothoraxes after percutaneous CT-guided core needle biopsy of the lung. Materials and methods: We performed a retrospective analysis of 868 CT-guided lung biopsies that were conducted at our institution between 2003 and 2018, of which 419 (48%) received an IBP. Outcome variable included the rates of pneumothorax and chest tube placement, as well as lesion size (<3 cm versus ≥3 cm long axis diameter), lesion depth (≤2 cm, >2-4 cm, >4-5 cm and >5 cm distance to the pleura), location within the lungs (upper lobe, lower lobe, middle lobe), needle caliber (13 G, 15 G, 17 G, 19 G), number of samples taken (1–3 versus ≥4 samples), and experience of the performing physician. Results: The rate of pneumothorax was significantly (p < 0.05) lower in the group with IBP (10.7%) compared to the group without IBP (15.4%). The number of post-interventional chest tube placements was also lower in the IBP group (3.1% vs. 5.8%) but not statistically significant. The lesion size correlated negatively with the rate of pneumothoraxes, whereas in both groups (±IBP) lesions ≥ 3 cm showed a significantly lower rate of pneumothorax (p < 0.05). With increasing lesion depth, the pneumothorax rate increased with (p < 0.01) and without (p < 0.001) IBP. The rate of pneumothorax was significantly lower (p < 0.05) for 17 G needles with IBP, but not for other calibers. For biopsies in the lower lobe, the pneumothorax rate reduced significantly (p < 0.001) with IBP. In case of ≥4 tissue samples, the pneumothorax rate was significantly lower with IBP (p < 0.01). For experienced operators, the overall pneumothorax rate was significantly lower compared to less experienced operators (p < 0001). Conclusions: IBP significantly reduces the rate of pneumothorax following CT-guided lung biopsies in particular for lesions located deeper in the lungs, when ≥4 samples are taken, when samples are taken by less-experienced operators, and when sampling from the lower lobes.